Postmortem interval estimation of human skeletonized remains through luminol chemiluminescence - Ermida, Catarina (2024)
Postmortem interval (PMI) estimation represents a significant challenge in the forensic sciences, particularly when dealing with human skeletal remains. A screening protocol for distinguishing possible remains of forensic interest is a crucial tool for judicial purposes. In this context, luminol chemiluminescence emerges as a promising method, with low overall costs and required time. This method is primarily used as a presumptive test, based on the understanding that the intensity of the chemiluminescence reactions decreases with an increase in the postmortem interval, thus underlining its practical implications. This research aims to expand previous research on the potential of luminol chemiluminescence, evaluating its usefulness in estimating PMI. Our sample comprised 239 human clavicles, with known PMI. The luminol solution was sprayed on each powder bone sample in a dark room, observed by the naked eye and photographed. The intensity of the chemiluminescence reaction was measured using a binary and a 5-level scale. The present results reveal that this method is a suitable tool for PMI estimation as a presumptive test, reducing time and costs in criminal investigations. The findings underscore the high sensitivity of luminol chemiluminescence for detecting recent PMI but also highlight a notable incidence of false positives. Thus, our results confirm luminol chemiluminescence as a powerful tool for dating time of death, particularly for identifying forensic relevant remains. Still, the relatively low specificity indicates that it should be complemented with additional tests for further confirmation and scientific validation of the remains’ forensic relevance.